Peran Hukum Internasional dan Perbatasan Wilayah Negara - Pudak Nayati (Unisia, 2005)
RecentlyIndonesia is facing the issues of the border with Malaysia. After facing the Sipadan and Ligitan conflict, Indonesia and Malaysia have been disputing to claim the Ambalat area. Aregion is an important factor of a country. The alteration of  the border of a region does not change the status of a country. Also, an unclear border of a region does not alternate the existence of a country. This paper describes some theories relating to the role of the International Law in a country's border. Some discusses the profile of the border of Indonesia relating to its neighboring countries,such as Thailand and Australia. This paper also analysis the role of the Intemational Law in the issue of country's border, particularly Indonesia, focusing the on the intemal and extemal functions of the International Law. The external function could be used as a base of Indonesian diplomacy at the international level. The intemal function would be utilizedas a tool to harmonize the National Law of Indonesia, however, this is not conducted yet.